2020
DOI: 10.1051/e3sconf/202014103002
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of Leafy Vegetables and Their Effects on Salmonella Attachment

Abstract: Leafy vegetables exhibit non-uniform surfaces and are structured with interconnected networks of veinlets or wrinkle characteristics, making the quantification of the changes rather difficult. In this study, attempt was made to quantify the surface topographical features of leafy vegetable. Image analysis was used to determine the characteristic of vegetable surface. In term of surface area (A), the results were compared with those correlated with the data obtained by a conventional measurement method. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Pathogens may come in contact with edible parts of crops and even be internalized in vegetable organisms ( Golberg et al, 2011 ; Riggio et al, 2019 ). The most frequently assessed bacterial pathogens were the Shiga toxin-producing E. coli (STEC) ( Deering et al, 2012 ; Koseki et al, 2011 ; Lopez-Galvez et al, 2014 ; Moriarty et al, 2019 ; Settanni et al, 2013 ), S. enterica ( Castro-Ibáñez et al, 2015 ; Nousiainen et al, 2016 ; Phungamngoen & Rittisak, 2020 ), and L. monocytogenes ( Sant’Ana et al, 2014 ; Y. J.; Wang et al, 2020 ). Irrigation water treatments ( Dandie et al, 2019 ), postharvest sanitation, and GMP are considered crucial in reducing such biological risks ( Olaimat & Holley, 2012 ; Trinetta et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens may come in contact with edible parts of crops and even be internalized in vegetable organisms ( Golberg et al, 2011 ; Riggio et al, 2019 ). The most frequently assessed bacterial pathogens were the Shiga toxin-producing E. coli (STEC) ( Deering et al, 2012 ; Koseki et al, 2011 ; Lopez-Galvez et al, 2014 ; Moriarty et al, 2019 ; Settanni et al, 2013 ), S. enterica ( Castro-Ibáñez et al, 2015 ; Nousiainen et al, 2016 ; Phungamngoen & Rittisak, 2020 ), and L. monocytogenes ( Sant’Ana et al, 2014 ; Y. J.; Wang et al, 2020 ). Irrigation water treatments ( Dandie et al, 2019 ), postharvest sanitation, and GMP are considered crucial in reducing such biological risks ( Olaimat & Holley, 2012 ; Trinetta et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of cabbage, 10 0 CFU/g could be detected by growth on EMB plates from 225 mL of extraction buffer. More E. coli O157:H7 was detected from cabbage than lettuce, which is thought to be due to the smooth surface of cabbage (Phungamngoen and Rittisak, 2020). The maximum amount of extraction buffer volume required to detect 10 0 CFU/g of E. coli O157:H7 by growth on EMB media was 50 mL and 225 mL in lettuce and cabbage, respectively.…”
Section: Bacterial Concentration By Reducing Extraction Buffer Volumementioning
confidence: 96%
“…Sher et al [6] analyzed the sources of outbreaks caused by Salmonella bacteria in the United States between 1990 -2015, and found that of 1,200 outbreaks, 96 (8%) were due to the consumption of contaminated vegetables. Leafy vegetables, which have a large surface area that can be colonized by Salmonella, are a particularly serious risk [17]. These vegetables are grown on a large scale, both in the field and under roof, and are exported fresh as well as minimally processed.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…The genus Salmonella, despite exposure to environmental stress, successfully persisted on the plant surface. This is also related to its production of cellulose and other polysaccharides, its ability to penetrate plant tissue, and its ability to incorporate into already existing multispecies biofilms [17].…”
Section: Colonisation Mechanism Of Plants By Salmonellamentioning
confidence: 99%